Application of 1, 4-bis(3-methylimidazolium-1-yl)butane ditribromide [bMImB]·(Br3)2 ionic liquid reagent for selective oxidation of sulfides to sulfoxides1. Issue 86 (18th September 2015) - Manesh, Abbas Amini; Eshbala, Fereshteh Hosseini; Hemmati, Saba; Veisi, Hojat
<x xml:space="preserve">Abstract</x> 1, 4-Bis(3-methylimidazolium-1-yl)butane ditribromide [bMImB]·(Br3)2 as an efficient reagent is used for the selective oxidation of dialkyl and alkyl aryl sulfides to the corresponding sulfoxides in high yields under mild conditions.